DEVELOPING MODELAUTHENTIC ASSESSMENT IN ELEMENTARY SCHOOL - Aditia Eska Wardana; Iis Nurasih; Luthfi Hamdani Maula (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
The purpose of this study is to: (1) analyze the factual model conditions, (2) designing a model of authentic assessment, (3) determine the validity of the model of authentic assessment and (4) assessing the practical of the final model of authentic assessment of learning process in elementary school of Margasari, Tegal. The method used is the Research and Development (R D), which consists of the preliminary study stage, stage of development and evaluation phase. Respondents are teachers. The model is validated by experts and practitioners with Delphi technique. Quantitative descriptive technique is applied to test Practicality of model that measures the ease aspects of the use models and benefits by giving questionnaires to the respondents to the teachers as users of the product. The results showed that: (1) the factual model condition of authentic assessment is still prioritizing aspects of knowledge as the basis of assessment, (2) the design of assessment model used authentic assessment based on the planning, implementation, and processing, (3) the validity of the authentic assessment model consists of validity learning device and assessment instruments. The validity of the learning device has a validity rate of 76.25% (good), while the validity of assessment instruments have a validity rate of 86% (excellent) and (4) practical authentic assessment models used in the assessment of Elementary School seen from the response of good teachers amounted to 89.8% (very practical).